A "quickscore" method for immunohistochemical semiquantitation: validation for oestrogen receptor in breast carcinomas. - Detre, S (1995)
Immunohistochemistry is increasingly used in the assessment of markers for breast cancer prognosis. Semiquantitation is frequently desirable but, other than by the use of image analysis, the approaches currently in use are cumbersome. The most common method used is the H-score which takes into consideration the staining intensity in conjunction with the percentage of cells staining positively in breast carcinoma tissue. A "quickscore" has been developed which dispenses with the need to count individual cells. The quantitative biochemical Abbott enzyme immunoassay (EIA) and the Dako immunohistochemical assay (IHA) incorporating a semiquantitative H-score, have been used as standards against which the IHA quickscore for the semiquantitation of oestrogen receptor expression was tested. A good correlation was found between the quickscore and the EIA, which was as good as that between the H-score and EIA. The quickscore is a valid approach and there is no advantage in using the more rigorous H-score. A positive cut off quickscore of > or = 3 has been suggested.